MEDI: Macronutrient Extraction and Determination from invertebrates, a rapid, cheap and streamlined protocol. Issue 4 (22nd January 2021) - Cuff, Jordan P.; Wilder, Shawn M.; Tercel, Maximillian P. T. G.; Hunt, Rhiannon; Oluwaseun, Somoye; Morley, Paige S.; Badell‐Grau, Rafael A.; Vaughan, Ian P.; Bell, James R.; Orozco‐terWengel, Pablo; Symondson, William O. C.; Müller, Carsten T.
Abstract: Macronutrients, comprising carbohydrates, proteins and lipids, underpin many ecological processes, but their quantification in ecological studies is often inaccurate and laborious, requiring large investments of time and bulk samples, which make individual‐level studies impossible. This study presents Macronutrient Extraction and Determination from Invertebrates (MEDI), a protocol for the direct, rapid and relatively low‐cost determination of macronutrient content from single small macroinvertebrates. Macronutrients were extracted by a sequential process of soaking in 1:12 chloroform:methanol solution to remove lipid and then solubilising tissue in 0.1 M NaOH. Proteins, carbohydrates and lipids were determined by colorimetric assays from the same individual specimens. The limits of detection of MEDI with the equipment and conditions used were 0.067, 0.065 and 0.006 mg/ml for proteins, carbohydrates and lipids respectively. Adjusting the volume of reagents used for extraction and determination can broaden the range of concentrations that can be detected. MEDI successfully identified taxonomic differences in macronutrient content between five insect species. Macronutrient Extraction and Determination from Invertebrates can directly and rapidly determine macronutrient content in tiny (dry mass ~3 mg) and much larger individual invertebrates. Using MEDI, the total macronutrient content of over 50 macroinvertebrates can be determined within around 3 days of collection at a cost of ~$1.35 per sample. Abstract: Mae macromaetholion, sy'n cynnwys carbohydradau, proteinau a lipidau, yn sail i lawer o brosesau ecolegol, ond mae eu meintioli mewn astudiaethau yn aml yn medru bod yn wallus ac yn llafurus, ac yn galw am fuddsoddiadau mawr mewn amser a swmp‐samplau. Gwna hyn astudiaethau ar lefel unigol yn amhosibl. Mae'r astudiaeth hon yn disgrifio MEDI (Echdyniad ac Adnabod Macromaetholion o Anifeiliaid Di‐asgwrn‐cefn), protocol newydd sy'n mesur ac adnabod macromaetholion yn uniongyrchol, ond yn gyflym ac yn gymharol rad, o facroinfertebratau bach sengl. Echdynnwyd macromaetholion trwy glain‐guriad mewn hydoddiant clorofform 1:12 methanol i waredu'r lipid, cyn hydoddi'r meinwe mewn 0.1M NaOH. Adnabuwyd proteinau, carbohydradau a lipidau gan brofion lliwmetrig o'r un sbesimenau. Cyfyngiadau darganfod MEDI gyda'r offer a ddefnyddiwyd oedd 0.067, 0.065 a 0.006 mg/ml ar gyfer proteinau, carbohydradau a lipidau, yn ôl eu trefn. Gall addasu cryfderau'r adweithyddion a ddefnyddir i echdynnu ac adnabod ehangu'r ystod o grynodiadau y gellir eu canfod. Llwyddodd MEDI i nodi gwahaniaethau tacsonomig mewn cynnwys macrofaetholion rhwng pum rhywogaeth o bryfed. Gall MEDI bennu cynnwys macromaetholion yn gywir, yn uniongyrchol ac yn gyflym, mewn anifeiliaid di‐asgwrn cefn bach (màs sych ~3 mg) a mawr. Gan ddefnyddio MEDI, gellir pennu cyfanswm cynnwys dros 50 o facromaetholion o fewn oddeutu tridiau am gost o tua $ 1.35 y sampl.